Absence of Ulnar Artery Inflow Detected by Allen's Test Prior to Radial Forearm Free Flap. Issue 4 (April 2017) - Taylor, Benjamin A.; Alzahrani, Faisal; Levi, Eric; Taylor, S. Mark; Rigby, Matthew H.; Trites, Jonathan; Hart, Robert D.
Abstract : Summary: Radial forearm free flaps are commonly used for soft-tissue reconstruction after resection of head and neck cancer. It is perfused by the radial artery, leaving the ulnar artery for perfusion of the hand and digits. The absence of distal ulnar artery and associated superficial palmar arch, however, has not been reported in cadaveric dissection. We report a case of unilateral ulnar artery flow absence, detected by Allen's test, during preoperative preparation for a radial forearm free flap. Based on the simplicity, safety, and ease, we recommend Allen's test to be performed preoperatively on every patient for whom such a flap is a consideration.